Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/jace.17933
|View full text |Cite
|
Sign up to set email alerts
|

Properties of SiC‐Si made via binder jet 3D printing of SiC powder, carbon addition, and silicon melt infiltration

Abstract: We report the physical and mechanical properties of ceramic composite materials fabricated by binder jet 3D printing (BJ3DP) with silicon carbide (SiC) powders, followed by phenolic resin infiltration and pyrolysis (IP) to generate carbon, and a final reactive silicon melt infiltration step. After two phenolic resin infiltration and pyrolysis cycles; porosity was less than 2%, Young's modulus was close to 300 GPa, and the flexural strength was 517.6 ± 24.8 MPa. However, diminishing returns were obtained after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…The binder was printed on the substrate using a piezo printhead (Polaris PQ‐512, Fujifilm) with a drop size of about 80 pl. The amount of binder per voxel was calculated as described by Cramer et al 52 . The binder was directly pre‐cured by the application of heat after the deposition and then the next slurry layer was applied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The binder was printed on the substrate using a piezo printhead (Polaris PQ‐512, Fujifilm) with a drop size of about 80 pl. The amount of binder per voxel was calculated as described by Cramer et al 52 . The binder was directly pre‐cured by the application of heat after the deposition and then the next slurry layer was applied.…”
Section: Methodsmentioning
confidence: 99%
“…The binder was printed on the substrate using a piezo printhead (Polaris PQ-512, Fujifilm) with a drop size of about 80 pl. The amount of binder per voxel was calculated as described by Cramer et al 52 The binder was directly pre-cured by the application of heat after the deposition and then the next slurry layer was applied. The binder was fully cured after the printing process to full strength for 16 h at 130 • C, like the casted samples, by placing the whole build volume into a furnace.…”
Section: Printing Trialsmentioning
confidence: 99%
“…Only a brief overview of various categories of 3D AM techniques for ceramic materials will be presented here, while more comprehensive information can be found in relevant review articles. [5][6][7] Although several 3D AM methods are routinely used for larger scale component manufacture, such as light induced polymerization based methods employing UV irradiation: Stere-oLithogrAphy (SLA), [8,9] Digital Light Proccessing (DLP), [10][11][12] deposition methods of Direct Ink Writing (DIW), [13] Ink Jet Printing (IJP), [14,15] Fused Deposition Modeling (FDM also know as Fused Filament Fabrication -FFF) [16,17] and Binder Jetting 3D Printing (BJ3DP) [18] or layered high-power laser based systems of Laminated Object Manufacturing (LOM) [19] and Selective Laser Sintering (SLS). [20] The listed techniques are allowing typical achievable feature sizes of tenths of micrometers [21][22][23] to millimeters in dimensions.…”
Section: Introduction: Concept Of Post-fabrication High-temperature T...mentioning
confidence: 99%
“…Interestingly, consistent with previous literature reports, all samples detected high‐order silicon peaks. [ 37 ] This means that silicon had a preferred orientation on the (111) crystal plane. Previous studies reported that PAN‐based carbon fiber reacted with molten silicon to form β ‐SiC at 1500 °C, and SiC crystals were precipitated from the carbon solution in liquid silicon during high temperatures, rather than after cooling.…”
Section: Resultsmentioning
confidence: 99%